Estresse ocupacional e transtornos mentais comuns entre professores universitários - Santos, Daniel Alberto Santos e (2016)
This dissertation presents the results of the research on Occupational Stress and Common Mental Disorders TMC among teachers of a public university in the interior of Bahia. In this research, three studies were developed in the form of articles. The first article aimed to problematize the process of commercialization in Brazilian universities and the effects of this process on teacher health. The second is cross-sectional, to estimate the prevalence of CMD and to identify factors associated with its occurrence. The prevalence of CCT was measured by the Self Report Questionnaire-20 (SRQ-20), and its association with sociodemographic characteristics and teacher work was assessed. The third article, with cross-sectional design, aimed to verify the association between Occupational Stress and Common Mental Disorders. Occupational stressors were measured by the Effort-Reward Imbalance Questionnaire (ERI). For the occurrence of CMT, SRQ-20 was used. In the first article, after the discussion of the problematic of working conditions and their impacts on the health of university professors, after successive neoliberal policies, it is understood that teachers started to live with a work environment based on business logic. Thus, the consequences are related to the intensification of work, leading to situations of overload, stress and competition. In this way, health and the use of time for leisure and rest become rare predicates in the daily life of this professional. The results of the analyzes carried out in the second article indicate an overall prevalence of MTC of 28%, being 30.2% among males and 26.0% among females. The prevalence of MCT was associated with not performing regular leisure activities, teaching for the doctorate, having less than 8 hours of sleep and availability of up to one hour for meals. In the third article higher prevalences of CMD were observed in situations of low reward and high effort at work. In situations of imbalance between effort and reward at work, the prevalence of CMD was 33.5%. The age group was identified as an interaction variable. In the analysis of the final model for the groups, the covariates that remained in the final analysis model were sex, leisure activity and marital status (potential confounders). There was no difference in the measures of association between teachers aged 25 to 46 years for the adjusted or unadjusted model. The situation differs greatly for the age group from 47 to 69 years. The statistically significant association remains in the adjusted model and with great magnitude: teachers with imbalance presented a prevalence of MCT almost six times higher than that observed among teachers with a balance between efforts and rewards. The discussion about the structure of teaching work conditions can provide elements for a critical thinking about the new configurations assumed in the work environment and the daily life of the professional, besides stimulating a reflection on the occupational health-illness process.